LIZ, Manuel (ed.) (2013): Puntos de Vista. Una investigación filosófica. Barcelona: Laertes. - Abraham Hérnandez Pérez (Daimon)
Reseña sobre el libro: LIZ, Manuel (ed.) (2013): Puntos de Vista. Una investigación filosófica. Barcelona: Laertes.